Mahesh Dattani’s Role in the Upliftment of the Marginalized Through Drama: A Critical Analysis - Ameer Ahmad Khan (Language, Literature and Education: Research Updates Vol. 1, 2025)
Indian writing in English has touched the peak of honour and glory in the fiction, prose and poetry genres, but the literary string of drama is quite weak. As compared to other genres by its specific nature, drama demands the two-fold significance of text and performance it has been in various forms and traditions, the folk, the mythical, the realistic, the epic and more. India after post-independence laid the foundation of a monarch genre by many famous dramatists like Girish Karnand, Vijay Tendulkar, Mohan Rakesh, and Badal Sircare but the present article is focused on the contribution of Mahesh Dattani’s role played as a dramatist in Indian dramatic Inheritance. The article investigates contemporary Indian drama in English literature as well as with a short historical brief. The drama genre in Indian English teaching has stunted growth that hurled endless debate on the academic platform. In spite of the paucity name of Mahesh Dattani is viewed, as one of the most famous Indian playwrights after Tagore and Aurobindo Ghose. Dattani is recognized as the dramatist of the pile, including the affluent, the oppressed the urban upper class and the deprived. Dattani’s famous dramas share a wide range of subjects related to the best option of Indian dramatic techniques. Dattani marks a distinction in Indian theatre for his credence to revealing issues like child sexual abuse, and alternate sexuality, and expands Indian theatre to bring it little adjacent to modern theatre at the international level. Finally, the article throws light upon the most successful facades of social and real-life plays written by Mahesh Dattani.